2011
DOI: 10.1002/star.201100017
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, crystalline, and thermal properties of native, oxidized, acid, and enzyme hydrolyzed Chinese yam (Dioscorea opposite Thunb) starch

Abstract: Native yam starch was modified by oxidation (with sodium hypochlorite), acid, and enzyme (with gluco‐amylase), respectively. Ash content, fat content, protein, and AM contents were reduced following modifications. All the modifications reduced swelling capacity whereas improved the solubility. The SEM of the native starch showed the presence of large oval or spherical to small irregular‐shaped granules, however, oxidation and hydrolysis caused collapse of the granules. From the XRD, the typical C‐type XRD patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 48 publications
2
5
0
1
Order By: Relevance
“…With respect to swelling power, the values found in the present study for oxidized starches (OS1–OS6 and OS9–OS12) were similar to those for NS (20.72 g/g), whereas the oxidized starches OS7 and OS8 obtained slightly lower swelling power values compared to that of NS. This reduction in swelling power of OS has also been reported in the oxidized starches of corn and Chinese yam . Xia et al indicated that the reduction in swelling power after oxidation with sodium hypochlorite may be attributed to the internal structural disintegration of the starch granule during the chemical modification process.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…With respect to swelling power, the values found in the present study for oxidized starches (OS1–OS6 and OS9–OS12) were similar to those for NS (20.72 g/g), whereas the oxidized starches OS7 and OS8 obtained slightly lower swelling power values compared to that of NS. This reduction in swelling power of OS has also been reported in the oxidized starches of corn and Chinese yam . Xia et al indicated that the reduction in swelling power after oxidation with sodium hypochlorite may be attributed to the internal structural disintegration of the starch granule during the chemical modification process.…”
Section: Resultssupporting
confidence: 61%
“…This reduction in swelling power of OS has also been reported in the oxidized starches of corn and Chinese yam . Xia et al indicated that the reduction in swelling power after oxidation with sodium hypochlorite may be attributed to the internal structural disintegration of the starch granule during the chemical modification process.…”
Section: Resultssupporting
confidence: 61%
“…The C‐type starch extracted from different plants shows distinct transition times; for example, kudzu starch has a more rapid hydrolysis‐induced crystal transformation than Chinese yam starch . In addition, oxidizing treatment utilizing sodium hypochlorite also contributed to the alteration of C‐ to A‐type crystallinity of yam starch . Thys et al .…”
Section: Modification Of C‐type Starchmentioning
confidence: 99%
“…Sodium hypochlorite is one of the most popular commercial reagents for starch oxidation, with such oxidized starch showing enhanced whiteness, water solubility, and contents of carbonyl and carboxyl; while swelling power, gel strength, crystallinity, and rheological parameters decrease . Oxidization procedures also lead to the collapse of starch granules, contributing to the transformation of the crystal pattern …”
Section: Modification Of C‐type Starchmentioning
confidence: 99%
“…1). Increase in paste clarity may be allied to granule size [35], the state of dispersion and the retrogradation tendency of the starch. Factors such as paste concentration, pH and granule structure are having influence on this paste clarity property [20].…”
Section: Paste Claritymentioning
confidence: 99%